VLBI Observations of Southern Gamma-Ray Sources. III. (26th February 2018) - Edwards, P. G.; Ojha, R.; Dodson, R.; Lovell, J. E. J.; Reynolds, J. E.; Tzioumis, A. K.; Quick, J.; Nicolson, G.; Tingay, S. J.
Abstract: We report the results of Long Baseline Array observations made in 2001 of ten southern sources proposed by Mattox et al. as counterparts to EGRET >100 MeV gamma-ray sources. Source structures are compared with published data where available and possible superluminal motions identified in several cases. The associations are examined in the light of Fermi observations, indicating that the confirmed counterparts tend to have radio properties consistent with other identifications, including flat radio spectral index, high brightness temperature, greater radio variability, and higher core dominance.